Laser‐Induced Cooperative Transition in Molecular Electronic Crystal. Issue 39 (16th August 2021) - Hu, Yong; Adhikari, Dasharath; Tan, Andrew; Dong, Xi; Zhu, Taishan; Wang, Xiaoyu; Huang, Yulong; Mitchell, Travis; Yao, Ziheng; Dasenbrock‐Gammon, Nathan; Snider, Elliot; Dias, Ranga P.; et al.
Abstract: The competing and non‐equilibrium phase transitions, involving dynamic tunability of cooperative electronic and magnetic states in strongly correlated materials, show great promise in quantum sensing and information technology. To date, the stabilization of transient states is still in the preliminary stage, particularly with respect to molecular electronic solids. Here, a dynamic and cooperative phase in potassium‐7, 7, 8, 8‐tetracyanoquinodimethane (K‐TCNQ) with the control of pulsed electromagnetic excitation is demonstrated. Simultaneous dynamic and coherent lattice perturbation with 8 ns pulsed laser (532 nm, 15 MW cm −2, 10 Hz) in such a molecular electronic crystal initiates a stable long‐lived (over 400 days) conducting paramagnetic state (≈42 Ωcm), showing the charge–spin bistability over a broad temperature range from 2 to 360 K. Comprehensive noise spectroscopy, in situ high‐pressure measurements, electron spin resonance (ESR), theoretical model, and scanning tunneling microscopy/spectroscopy (STM/STS) studies provide further evidence that such a transition is cooperative, requiring a dedicated charge–spin–lattice decoupling to activate and subsequently stabilize nonequilibrium phase. The cooperativity triggered by ultrahigh‐strain‐rate (above 10 6 s − 1 ) pulsed excitation offers a collective control toward the generation and stabilization of strongly correlated electronic and magnetic orders in molecular electronic solids and offers unique electro‐magnetic phases with technological promises. Abstract : A major challenge in a supramolecular electronic crystal is switchable control of its hidden phase. The cooperative tuning of K‐TCNQ through a pulsed electromagnetic field into an emergent electronic disorder state, enabling access to a long‐lived (over 400 days) hidden conducting phase, is found. A switchable magneto‐electronic bistability is realized in a broad temperature range from 2 to 360 K.